Immobilization of Glycogen Synthase Kinase-3β Inhibitor on 316L Stainless Steel via Polydopamine to Accelerate Endothelialization - Zhang, Ming; Shi, Xudong; Sun, Hai; Xu, Donghua; Gao, Yang; Wu, Xi; Zhang, Jianqi; Zhang, Jichang (Frontiers in Bioengineering and Biotechnology, 2021)
The coverage of stents with healthy endothelium is crucial to the success of cardiovascular stent implantation. Immobilizing bioactive molecules on stents is an effective strategy to generate such stents. Glycogen synthase kinase-3β inhibitor (GSKi) is a bioactive molecule that can effectively accelerate vascular endothelialization. In this work, GSKi was covalently conjugated on 316L stainless steel through polydopamine to develop a stable bioactive surface. Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and water contact angle results revealed the successful introduction of GSKi onto 316L stainless steel. The GSKi coating did not obviously affect the hemocompatibility of plates. The adhesion and proliferation of human coronary artery endothelial cells (HCAECs) on stainless steel was significantly promoted by the addition of GSKi. In summary, this work provides a universal and stable strategy of immobilizing GSKi on the stent surface. This method has the potential for widespread application in the modification of vascular stents